Inhibition of GSK3β Modulates Cell Death in Epithelial Ovarian Cancer - Naeha Pathak; Tyler Walther; Noelle Cutter (European Scientific Journal, ESJ, 2016)
Epithelial ovarian cancer is one of the most common gynecological malignancies and the fifth most frequent cause of cancer death in women, affecting over 22,000 women annually. Nearly 15,500 affected women die from this disease annually, and chemoresistance from the commonly prescribed platinum-based drug, carboplatin, is a major contributor to this mortality rate. Previous studies have identified genes with CpG islands that are methylated and transcriptionally silenced in resistant epithelial ovarian cancer patients. One of these genes is GSK3β, an important regulator of apoptosis and cell growth in the Wnt pathway. Thus, understanding the role of GSK3β suppression in chemoresistance of epithelial ovarian cancer can help contribute to more effective treatments for this disease. By performing assays of cell growth, viability, and apoptosis, our study examined the functional role that GSK3β plays in carboplatin mediated apoptosis. Our results suggest that cells with suppressed GSK3β had increased proliferation and reduced apoptosis. We conclude that silenced GSK3β expression might therefore contribute to carboplatin resistance seen in tumors and our in vitro analysis suggests that GSK3β expression is vital to carboplatin chemosensitivity. Future research is required to further investigate the role of GSK3β methylation to facilitate the design of potential genome-guided treatments for patients with chemoresistant epithelial ovarian cancer.